Justifications for Non-Consensual Medical Intervention: From Infectious Disease Control to Criminal Rehabilitation. Issue 3 (1st September 2016) - Pugh, Jonathan; Douglas, Thomas
Abstract : A central tenet of medical ethics holds that it is permissible to perform a medical intervention on a competent individual only if that individual has given informed consent to the intervention. Yet it occasionally seems morally permissible to carry out non-consensual medical interventions on competent individuals for the purpose of infectious disease control (IDC). We describe two different moral frameworks that have been invoked in support of non-consensual IDC interventions and identify five desiderata that might be used to guide assessments of the moral permissibility of such interventions on either kind of fundamental justification. We then consider what these desiderata imply for the justifiability of carrying out non-consensual medical interventions that are designed to facilitate rehabilitation amongst serious criminal offenders. We argue that these desiderata suggest that a plausible case can be made in favor of such interventions.